Do Auditors Accurately Predict Litigation and Reputation Consequences of Inaccurate Accounting Estimates? - Gimbar, Christine; Mercer, Molly (Contemporary Accounting Research, 2021)
ABSTRACT To effectively manage audit risk, auditors must correctly predict the potential litigation and reputation consequences associated with inaccurate accounting estimates. Accurate predictions are critical because underestimation of negative consequences leads to excess legal exposure and overestimation leads to overauditing. Our paper examines whether auditors correctly anticipate these litigation and reputation outcomes. We provide manager‐ and partner‐level auditors with case facts from an auditor negligence lawsuit and ask them to predict the proportion of juries that will return verdicts against their firm. We then compare auditors' predictions to the actual verdicts we observe when we provide the same set of case facts to mock jurors who deliberate as part of juries. We find that auditors overestimate the likelihood of negligence verdicts, especially when audit quality is relatively high. Our supplemental measures help explain the reasons for this overestimation: auditors tend to underestimate jurors' perceptions of audit quality and willingness to attribute inaccurate estimates to situational factors. Finally, we examine auditors' predictions about how a news article about the litigation will affect their reputation with the general public. Similar to our litigation results, we find that auditors tend to overestimate the article's negative impact on auditor reputation. Collectively, our findings suggest that auditors overestimate litigation and reputation consequences resulting from inaccurate accounting estimates. This overestimation is consequential as it leads to inefficient allocation of audit resources.